2019
DOI: 10.3389/fnagi.2019.00243
|View full text |Cite
|
Sign up to set email alerts
|

Appoptosin Mediates Lesions Induced by Oxidative Stress Through the JNK-FoxO1 Pathway

Abstract: Oxidative stress is a common feature of neurodegenerative diseases and plays an important role in disease progression. Appoptosin is a pro-apoptotic protein that contributes to the pathogenesis of neurodegenerative diseases such as Alzheimer's disease and progressive supranuclear palsy. However, whether appoptosin mediates oxidative stress-induced neurotoxicity has yet to be determined. Here, we observe that appoptosin protein levels are induced by hydrogen peroxide (H2O2) exposure through the inhibition of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Oxidative stress is a major trigger of follicular atresia and GC apoptosis which impairs follicular development, leads to a variety of ovarian diseases, and limits the fertility of female animals including pigs [ 49 , 50 , 51 ]. FoxO1 is a major sensor and effector of oxidative stress [ 52 ] which can promote cell apoptosis in response to oxidative stress by activating downstream apoptosis-related proteins such as Bim [ 53 ], P21 [ 54 ], and Fasl [ 55 ]. Similarly, it has also been reported that inhibiting FoxO1 by different means can effectively block the effect of oxidative stress [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is a major trigger of follicular atresia and GC apoptosis which impairs follicular development, leads to a variety of ovarian diseases, and limits the fertility of female animals including pigs [ 49 , 50 , 51 ]. FoxO1 is a major sensor and effector of oxidative stress [ 52 ] which can promote cell apoptosis in response to oxidative stress by activating downstream apoptosis-related proteins such as Bim [ 53 ], P21 [ 54 ], and Fasl [ 55 ]. Similarly, it has also been reported that inhibiting FoxO1 by different means can effectively block the effect of oxidative stress [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The c-Jun N-terminal kinase (JNK) signaling cascade is triggered in response to a broad spectrum of stressors 49 . Of particular relevance to AD, JNK-MAPK proteins are involved in the regulation of apoptosis during oxidative damage through phosphorylation of effector proteins or transcription factors, which may lead to dysregulation of tau phosphorylation and accumulation of hyperphosphorylated tau, the major component of NTs 50 , 51 . The transcription factor SP1 also responds to inflammatory signals, such as those induced by neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that FOXO1 critically regulates oxidative stress-induced cellular death. It triggers apoptosis under oxidative stress and increases the expression of apoptosis-promoting genes ( Zhang et al, 2019 ). Li et al found that melatonin inhibits TM3 cells’ autophagy caused by H 2 O 2 via the AKT/FOXO1 pathway ( Li et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%